Microglial subtypes: diversity within the microglial community - Stratoulias, Vassilis; Venero, Jose Luis; Tremblay, Marie‐Ève; Joseph, Bertrand (The EMBO journal, 2019)
Microglia are brain‐resident macrophages forming the first active immune barrier in the central nervous system. They fulfill multiple functions across development and adulthood and under disease conditions. Current understanding revolves around microglia acquiring distinct phenotypes upon exposure to extrinsic cues in their environment. However, emerging evidence suggests that microglia display differences in their functions that are not exclusively driven by their milieu, rather by the unique properties these cells possess. This microglial intrinsic heterogeneity has been largely overlooked, favoring the prevailing view that microglia are a single‐cell type endowed with spectacular plasticity, allowing them to acquire multiple phenotypes and thereby fulfill their numerous functions in health and disease. Here, we review the evidence that microglia might form a community of cells in which each member (or “subtype”) displays intrinsic properties and performs unique functions. Distinctive features and functional implications of several microglial subtypes are considered, across contexts of health and disease. Finally, we suggest that microglial subtype categorization shall be based on function and we propose ways for studying them. Hence, we advocate that plasticity (reaction states) and diversity (subtypes) should both be considered when studying the multitasking microglia. Graphical Abstract Bertrand Joseph and colleagues discuss the complexities and heterogeneity of the resident macrophage cells that play key roles in CNS immune responses, suggesting function‐based categorizations and ways for further studies.